Pharmacy graduates’ chronicle in Malaysia: Balancing CGPA and soft skills / Azyyati Mohd Suhaimi - Mohd Suhaimi, Azyyati (Penerbit UiTM (UiTM Press), 2017)
Liberalisation of Provisionally Registered Pharmacist (PRP) training in Malaysia has recently been extended to the private facilities recognized by the Pharmacy Board Malaysia (PBM). This has increased the number of graduate employment opportunities. Pharmacy graduates are required to undergo an interview with the Public Services Commission of Malaysia (PSC) and are not allowed to work as pharmacists unless they pass the provisional training. Selection of candidates to be called for interview is generally dependent on their Cumulative Grade Point Average (CGPA). Success at the interview, however, is based on their overall performance and not simply on their CGPA. The chances of success at interview are enhanced by their ability to combine their theoretical knowledge learnt at university with soft skills such as good communication and emotional intelligence. This paper outlines the importance of soft skills and offers suggestions as to how Malaysian pharmacy graduates can enhance them.